Enhanced CO oxidation on CeO2/Co3O4 nanojunctions derived from annealing of metal organic frameworks. Issue 47 (22nd November 2016) - Wang, Changlai; Wang, Dongdong; Yang, Yang; Li, Ren; Chen, Changle; Chen, Qianwang
Abstract : Unique nano heterojunction structures with numerous interfaces are synthesized in situ by one-step annealing of Metal–organic frameworks (MOFs), which exhibit remarkable catalytic activity towards CO oxidation. Abstract : The interface of nanojunctions plays an important role in the performance of heterogeneous catalysts. However, it is highly challenging to construct nanojunctions which are usually prepared by complex multistep processes. Metal–organic frameworks (MOFs), with designable metal centers and tunable organic ligands, are promising precursors for the one-step synthesis of nanojunctions. Herein, we prepared porous CeO2 /Co3 O4 nanojunctions by direct annealing of MOFs in air. These unique nanojunctions exhibit remarkable catalytic activity for CO oxidation, which can achieve complete oxidization of CO to CO2 at 110 °C. In contrast, the temperature required for 100% CO oxidation is 190 °C for pure Co3 O4 . Moreover, the nanojunctions can maintain complete CO conversion after 16 h at 110 °C. Density functional theory calculations revealed that the enhancement in the catalytic activity of CeO2 /Co3 O4 nanojunctions can be attributed to the charge transfer through the interfaces of the nanojunctions.